STUDENTS’ INTRINSIC MOTIVATION USING GAME-BASED ACTIVITIES - Nestor L. Lasala Jr (Tạp chí Khoa học Đại học Đà Lạt)
This study sought to determine the effects of game-based activities (GBAs) on students’ intrinsic motivation. The study employed a sequential explanatory mixed-methods approach using quantitative and then qualitative data to explore the impact of GBAs on intrinsic motivation. It also utilized lessons integrating GBAs into an ecosystem curriculum developed and adapted by the researcher for the study. Sixty-nine Grade 7 students from two sections of a public secondary school in Sorsogon, Philippines, participated in this study. One section with 34 students was assigned to an experimental group and exposed to GBAs developed for ecosystem lessons. The 35 students in the other section were assigned to a control group and taught with games using traditional teaching methods. Respondents completed a survey on the intrinsic motivation inventory (IMI) after the intervention. The survey results revealed a significant difference in the IMI scores of respondents (u = 327, N = 69, p = 0.05), and the integration of GBAs in ecosystem lessons for Grade 7 significantly improved students’ intrinsic motivation. Qualitative data analysis also revealed that GBAs specifically addressed students’ psychological needs in terms of interest or enjoyment, perceived competence, effort or importance, value or usefulness, and relatedness, which ultimately improved students’ intrinsic motivation. Integration of GBA into ecosystem lessons can improve students’ intrinsic motivation when GBAs align with learning goals and include interactive and engaging game elements. This study emphasized the effects of GBAs on intrinsic motivation and delved deeper into the specific context of science education in Grade 7, providing insights on how to harness GBAs effectively in specific educational settings. This study recommends the integration of GBAs into science education to enhance students’ motivation and improve their learning experiences and outcomes. A more comprehensive study of the effect of GBAs on students’ learning experiences is also recommended.